Metabolomics and its Applications in Cancer Cachexia - Cui, Pengfei; Li, Xiaoyi; Huang, Caihua; Li, Qinxi; Lin, Donghai (Frontiers in Molecular Biosciences, 2022)
Cancer cachexia (CC) is a complicated metabolic derangement and muscle wasting syndrome, affecting 50-80% cancer patients. So far, molecular mechanisms underlying CC remain elusive. Metabolomics techniques have been used to study metabolic shifts including changes of metabolite concentrations and disturbed metabolic pathways in the progression of CC, and expand further fundamental understanding of muscle loss. In this article, we aim to review the research progress and applications of metabolomics on CC in the past decade, and provide a theoretical basis for the study of prediction, early diagnosis, and therapy of CC.